The Historical Anakim in Egyptian, Biblical and Ugaritic Sources - Korpelainen, Eirik E. (Orientalia, 2024)
This article explores the historicity of the ancient population called the Anakim. Besides their hitherto acknowledged attestations in the biblical and Egyptian records, I will show that the Anakim also appear in Ugaritic literature. Far from being the mythical giants of past theological interpretations, they were an important and enduring historical people of the Middle and Late Bronze Age Levant. The Egyptians and Israelites deemed them awe-inspiring enemies, whereas at Ugarit, and among the Israelites, they were viewed as forebears to the Philistine people. Particularly distinctive to the Anakim was their seemingly perennial nomadism and the triumvirate-like quality of their rulership. Over time they transformed from a more overtly Semitic Amorite population into an increasingly Hurrian-influenced one. Both biblical and Ugaritic sources associated the Anakim with Rephaim. Eventually, they merged with the inhabitants of Philistia or otherwise disappeared from the historical record.